2004
DOI: 10.1073/pnas.0308141101
|View full text |Cite
|
Sign up to set email alerts
|

Nonvesicular release of acetylcholine is required for axon targeting in theDrosophilavisual system

Abstract: We report evidence for a developmental role of acetylcholine in axon pathfinding in the Drosophila visual system. Acetylcholine was detected on photoreceptor axons during their navigation to target sites in the brain, a time well before the formation of functional synapses. The pattern of photoreceptor axon projections was severely disrupted when acetylcholine synthesis or metabolism was altered or eliminated, or when transgenic ␣-bungarotoxin, a nicotinic acetylcholine receptor antagonist, was expressed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Previous experiments with munc18-1 null mice, which have no regulated secretion of a neurotransmitter, also suggested that NMJ development is reg- ulated by synaptic vesicle exocytosis, although for these mutants, it has not been established whether ACh synthesis and storage are affected (28). A number of previously reported studies suggested that distinct pathways of ACh secretion might exist at cholinergic synapses (56,60,61,64). Moreover, vesamicol-independent ACh release, presumably from synaptic vesicles, can be detected in response to pharmacological treatments (2,7,10,11,46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments with munc18-1 null mice, which have no regulated secretion of a neurotransmitter, also suggested that NMJ development is reg- ulated by synaptic vesicle exocytosis, although for these mutants, it has not been established whether ACh synthesis and storage are affected (28). A number of previously reported studies suggested that distinct pathways of ACh secretion might exist at cholinergic synapses (56,60,61,64). Moreover, vesamicol-independent ACh release, presumably from synaptic vesicles, can be detected in response to pharmacological treatments (2,7,10,11,46).…”
Section: Discussionmentioning
confidence: 99%
“…Quantal ACh release, comparable to that seen in developing nerve terminals, has been detected in myocytes and fibroblasts in culture, which presumably do not express VAChT (14,24). More recently, it was found that the correct targeting of Drosophila photoreceptor axons is disrupted in flies with null mutations in ChAT (64). Remarkably, the inactivation of VAChT did not produce the same result (64).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Selective antagonism of muscarinic receptors is neuroprotective in peripheral neuropathy opment (22,23). In mammals, cell bodies of sensory neurons synthesize and secrete ACh (24), express a peripheral form of choline acetyltransferase (pChAT), exhibit ChAT activity, have low acetylcholinesterase (AChE) activity, and express multiple muscarinic receptors including muscarinic Ach type 1 receptor (M 1 R) (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the neurotransmitter acetylcholine (ACh) is released from embryonic motor neurons (MNs) at the neuromuscular junction (NMJ), and it negatively regulates survival, axon branching, and synapse formation (4)(5)(6)(7). ACh is also released from developing neurons even before they arrive at their target, and it acts in an autocrine and/or paracrine fashion to regulate growth (8), pathfinding (9), spontaneous activity (10), and target selection (11). Whereas the NMJ has served as an excellent model to elucidate the process of synapse formation, the cellular and molecular mechanisms by which ACh regulates this process are still unclear; this is in part because the expression of ACh receptor (AChR) subtypes varies over space and time during the development of this synapse.…”
mentioning
confidence: 99%